The Neuronal Hypofunction of Subdivisions of the Prefrontal Cortex Shows Differential Effects on Contingency Judgment Learning to Gauge Fear Responses - Tyler W Bailey; John H Speigel; Johannes Mayer; Edward Korzus (Neuroscience Insights)
Previous studies have indicated that the infralimbic (IL) and prelimbic (PL) subdivisions of the medial prefrontal cortex (mPFC) serve as critical modulators of fear suppression and expression. Although significant research has been conducted on the extinction of conditioned fear, the mechanisms underlying contextual fear discrimination learning, a form of contingency judgment learning, remain inadequately understood. Our investigation aimed to explore the influence of epigenetic regulation associated with cyclic AMP-response element binding protein (CREB)-dependent long-term memory encoding within the IL and PL on contextual fear discrimination. Our prior and current findings illustrate that epigenetic hypofunction induced by a CREB-Binding Protein (CBP) mutant, which is deficient in histone acetyltransferase activity (CBPΔHAT), within the mPFC leads to compromised contextual fear discrimination while not affecting contextual fear conditioning in these mutants. Unexpectedly, the effect was not noticeable when the hypofunction was constrained to the infralimbic (IL) area; however, the hypofunction of the prelimbic (PL) network led to considerable impairment in fear discrimination. The findings indicate that learning fear discrimination involves differential encoding across the specialized networks of the mPFC. These data suggest that the IL network is not essential for encoding during the acquisition and discrimination of fear or that the PL network may compensate for the IL’s inability to encode new information. Furthermore, these results emphasize the importance of histone acetylation in the mPFC as a crucial physiological mechanism for learning contingency judgment.